Identifikasi jenis-jenis pisang (Musa sp) di Distrik Kepulauan Aruri Kabupaten Supiori Provinsi Papua - Ningsi, Ratna; Rumbekwan, Yusthinus; Widodo, Imam; Lenda Mawikere, Nouke; Purbokurniawan; Yanti Andriyani, Liz (Cassowary, 2026)
This study aims to identify the types of bananas found on Auri Island, Supiori Regency. This research was conducted in Mburwandi, Manggonswan, Insumbrei, Sawendi, Aruri, Imbirsbari, and Ineki villages. The data collected consisted of qualitative and quantitave banana plant characters observed directly in the field. The similarity among banana types was analyzed using cluster analysis and the results were presented in the form of dendrograms and descriptive tables. The findings indicate that there are 11 types of bananas distributed across the seven villages in the Auri Island District. Cluster analysis revealed seven similarity groups. Cluster 1 consisted of Pisang Nona, while Cluster 2 comprised Pisang Mas and Pisang Raja, which formed a closely related group based on shared characteristics, particularly the presence of speckles on the leaf petiole, leaf color, the color of the upper leaf surface, the color of the lower leaf surface, and fruit shape. Cluster 3 included Pisang Insarek, whereas Cluster 4 consisted of Pisang Kidang and Pisang Seribu, which exhibited similarities in leaf posture, waxy layer, lower leaf surface color, and fruit shape. Cluster 5 comprised Pisang Ambon, Cluster 6 included Pisang Kepok, characterized by a waxy surface and tapering fruit shape, and Cluster 7 consisted of Pisang Jarum. This variation among clusters indicates the substantial potential of banana genetic resources, which is essential for conservation efforts and banana breeding programs.